โครงการวิจัยพัฒนาแบบประเมิน CERAD เพื่อการวินิจฉัยและลงทะเบียนผู้ป่วยอัลไซเมอร์ไทย - สุขเจริญ ตั้งวงษ์ไชย (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
CERAD (The Consortium to Establish a Registry for Alzheimer s Disease) is the world wide standard instrument for assessment of Alzheimer s disease. The neuropsychological battery provides the information about the cognitive profiles of the patients which aide in diagnose and long-term follow up of these patients. This project aims to develop and validate the CERAD -Thai version, and develop the electronic version that enable the online users to register the patients. Method: This was the descriptive and diagnostic test study. The researchers asked for permission to translate and validate the CERAD to Thai version from Center for the Study of Aging and Human Development, Duke University Medical Center, USA. The content and language were validate by the experts. Total I g2 subjects have been recruited at the outpatient department, King Chulalongkom Memorial hospital. The clinical assessment and diagnosis have been performed by attending psychiatrists and neurologists at the dementia clinic, King Chulalongkom Memorial hospital. In the screening period, the TMSE( Thai Mental State Examination) ,TGDS ( Thai Geriatric Depressive Scale), CDR ( Clinical Dementia Rating Scale) were used for recruitment, according to the inclusion and exclusion criteria. The CERAD -Thai version, were used to register the patients by trained clinicians. The sample were collected blood sample to perform the ApoE genotyping. The outcomes were analyzed with SPSS version 16 for descriptive statistics and the validity of CERAD neuropsychological battery (J module). Resu It: The project was accomplished by recruiting 182 subjects, including 62 normal elderly, 60 patients with MCI and 60 patients with Alzheimer S disease ( AD). The sample had the mean age of 73.86 ±7.68 years old and 74.6 % were female. Most of them were married or widow (44.5 % and 36.3%) The mean year of education was 9.8 ± 5.H3 years. It was found that the AD group had older age, fewer year of education, more widows and more likely to live with their family without the spouse than another two groups. Hypertension (44 %), OM ( 18.7% ) and heart disease ( 9.3% ) were the most frequent medical comorbidity in this sample. There were 58 and 2 patients with alzheimer s disease had CDR stage I and 2, respectively. The cognitive profiles from the CERAD J module were demonstrated that The AD group had statistically lowest mean score of MMSE and CERAD sum score comparing to MCI and normal elderly group. The mean CERAD sum score of the AD, the MCI and normal control were 36.88 ± 10.75,72.80 ± 11.34 and 84.39 ± 5.88. The CERAD sum score could differentiate the 3 groups better than the MMSE score. The cut off score below 62 yielded the sensitivity of 1.0 and specificity of 082 for discriminating the patients with A and normal controls and the cut off score below 81 had the sensitivity of 0.73 and specificity of 0.7 in diagnosis of MCI. The ApoE 3 was the most frequent allele found in all 3 groups ( 44.3%). The ApoE 4 genotyping was found to be more frequent in AD group and increased 9.38 fold risk for AD. Conclusion: The project of development of CERAD Thai version, was successfully implemented as plan. The result showed that CERAD-Thai version was applicable in registering the patients with AD . The CERAD neuropsychological battery seemed to be able to distinguish the patients with Alzheimer s disease from patients with MCI and normal elderly with good validity. ApoE 4 genotyping was demonstrated to be risk in Alzheimer s disease in these samples.